A lab-based study to assess the surface roughness of various investments: An original research - Harisha Dewan; Vishwanath Gurumurthy; Vilas V Patel; Sirisha Kommuri; Ruthika S Patil; Sowgata Debsingha (Wolters Kluwer Medknow Publications, 2024)
Introduction: Surface roughness of the crowns is dependent on the pattern material used for the making as well as the procedure of investing. The study was aimed to examine the impact of various pattern materials and investment procedures on the surface roughness of nickel-chromium alloy raw castings. Materials and Methods: An in-vitro study was piloted at a tertiary care hospital. Eighty samples of inlay wax and pattern resin were divided equally. They were invested in phosphate-bonded investment material and kept under normal atmospheric pressure as well as invested under a pressure of 3 bars. The surface roughness was calculated with a Profilometer. The values obtained were compared using statistical tools keeping P < 0.05 as significant. Results: Lowest surface roughness was seen for the wax pattern invested under positive pressure. While the highest was seen for the resin patterns invested at room pressure. A significant variance between the wax 1 and wax 2 (P < 0.01); as well as between the wax 2 vs. Resin 2 specimens (P < 0.01) was noted. Conclusions: Wax patterns can be suggested as the material and method of choice because they showed the least amount of surface roughness when placed under pressure. Resin patterns when invested under pressure can also be suggested as an alternate as they also exhibited similar surface roughness as that of the wax.